2003
DOI: 10.1067/mhn.2003.52
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Laryngopharyngeal Sensory Deficits, Pharyngeal Motor Function, and the Prevalence of Aspiration with Thin Liquids

Abstract: Patients with severely diminished laryngopharyngeal sensation and pharyngeal motor function are at an extremely high risk of aspirating thin liquids (100%). Moderate sensory deficits only appear to influence the prevalence of thin liquid aspiration in the presence of pharyngeal motor dysfunction. Severe laryngopharyngeal sensory deficits are associated with the aspiration of thin liquids regardless of the integrity of pharyngeal motor function. We assume that all persons with an insensate laryngopharynx aspira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
59
1
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 11 publications
3
59
1
3
Order By: Relevance
“…Lastly, by definition, patients with motor neuron disease are without sensory deficits. Therefore, endoscopic sensory assessment of the laryngopharynx, although reported to be predictive of airway protection without administration of a food bolus [15], may not be optimal for the evaluation of swallowing in the ALS population.…”
Section: Discussionmentioning
confidence: 95%
“…Lastly, by definition, patients with motor neuron disease are without sensory deficits. Therefore, endoscopic sensory assessment of the laryngopharynx, although reported to be predictive of airway protection without administration of a food bolus [15], may not be optimal for the evaluation of swallowing in the ALS population.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, several clinical studies confirmed the impact of sensory feedback by using oropharyngeal anesthesia [2,5,15,16]. A study using flexible endoscopic evaluation of swallowing with sensory testing (FEESST) in dysphagic patients showed that severe laryngopharyngeal sensory deficits resulted in aspiration of liquids regardless of the pharyngeal motor function [36]. This points to the outstanding role of sensory input in swallowing.…”
Section: Discussionmentioning
confidence: 99%
“…Sensory deficits generally compound the effects of motor deficits associated with RLN injury. Indeed, the most severe forms of swallowing impairment are classically associated with combined injuries to both the RLN and the superior laryngeal nerve (SLN), because of additional loss of laryngeal sensory input with SLN damage [17,21,22]. This appears to have been the case with Patient No.…”
Section: Discussionmentioning
confidence: 94%